Trends and determinants of inequities in childhood stunting in Bangladesh from 1996/7 to 2014 - Rabbani, Atonu; Khan, Akib; Yusuf, Sifat; Adams, Alayne (© 2016 International Journal for Equity in Health, 2018)
This article was published in the International Journal for Equity in Health [© 2016 The Author(s) ] and the definite version is available at : https://doi.org/10.1186/s12939-016-0477-7. The Journal's website is at: https://equityhealthj.biomedcentral.com/articles/10.1186/s12939-016-0477-7#Abs1